Anomalous Levels of CD47/Signal Regulatory Protein Alpha in the Hippocampus Lead to Excess Microglial Engulfment in Mouse Model of Perioperative Neurocognitive Disorders - Shui, Min; Sun, Yi; Lin, Dandan; Xue, Ziyi; Liu, Jianhui; Wu, Anshi; Wei, Changwei (Frontiers in Neuroscience, 2022)
Background Perioperative neurocognitive disorders (PNDs) are common complications of surgical patients, which can lead to prolonged hospitalization, increased complications, and decreased independence and quality of life. However, the underlying molecular mechanisms of PND remain largely obscure. Microglia activation and synapse loss were observed in PND. Cluster of differentiation 47 (CD47), which can bind to its receptor signal regulatory protein alpha (SIRPα) and generate “do not eat me” signal, protects synapses from excessive pruning. Therefore, we aimed to evaluate the potential role of CD47–SIRPα signaling in PND. Methods The tibial fracture surgery was performed in aged C57BL/6 mice for PND model establishment. The expression of CD47 and SIRPα in the hippocampus was assessed. Synaptic plasticity, dendritic spine density, microglial engulfment, and hippocampal-dependent memory function were evaluated after model establishment and intervention with SIRPα overexpression. Results CD47 and SIRPα expression in the hippocampus were both decreased after the surgery. SIRPα overexpression showed reduced engulfment within host microglia, but a total effect of excessive synapse engulfment decreased dendritic spine density and post-synaptic density protein 95 (PSD95) expression. SIRPα overexpression could not improve the synaptic dysfunction and cognitive impairment in PND. In addition, SIRPα overexpression led to increased CD47 and Iba1 expression. Conclusion Anesthesia and surgery affect CD47–SIRPα signaling. SIRPα overexpression could not ameliorate the cognitive impairment in PND mice. One reason may be that the increased Iba1 expression leads to a total effect of excessive synapse engulfment, which results in decreased dendritic spine density and PSD95 expression.